The role of contrast sensitivity in global motion processing deficits in the elderly - Allen, Harriet A.; Hutchinson, Claire V.; Ledgeway, Tim; Gayle, Precius (Association for Research in Vision and Ophthalmology, 2010)
This study compared the effects of age on the perception of translational, radial, and rotational global motion patterns. Motion coherence thresholds were measured for judging the direction of each motion type as a function of contrast (visibility) and temporal sampling rate in young and elderly participants. Coherence thresholds decreased as dot contrast increased asymptoting at high dot contrasts but were higher in elderly compared to young participants. This equated to global motion impairment in the elderly of a factor of around 2, characterized by a shift of the threshold vs. contrast function along the horizontal axes (dot contrast). The effect of contrast interacted with the temporal sampling rate. Old participants were deleteriously affected by reduced temporal sampling particularly at low contrasts. The findings suggest that age- related changes in global motion perception may be driven principally by deficits in contrast encoding, rather than by deficits in motion integration and suggest a role for increased internal noise in the older visual system.